Pelatihan Teknik Ecoprint Sebagai Alternatif Peluang Usaha - Hendrayanti, Silvia; Fauziyanti, Wachidah; Puji Estuti, Eni (LPPM Universitas Bina Sarana Informatika, 2023)
Currently, MSME products continue to grow and develop, in fact some types of products are developing very rapidly in line with market demand trends. The textile industry is one of the contributors to the highest amount of waste or rubbish in the world. One of the wastes produced by the textile industry is liquid waste in the form of residual dyes/synthetic dye liquid from the fabric dyeing process which contains several dangerous chemical substances. As time goes by and technology continues to develop, synthetic dyes for textiles have been discovered. Synthetic dyes produce dangerous waste which can cause environmental pollution, such as contaminating the surrounding soil, sediment and surface water. Ecoprint products do have their own uniqueness and appeal. The application of the eco friendly concept, aka environmentally friendly products and their sustainable nature, is attractive to those who support a sustainable and environmentally friendly lifestyle. If many years ago an environmentally friendly lifestyle was popular abroad, now in Indonesia there are also many similar campaigns. This creates very open business opportunities for ecoprint products, both at home and abroad. Entrepreneurial training, especially in the field of ecoprint business management in the RW 08 area, Krapyak Subdistrict, West Semarang District, is a consideration for the Semarang College of Economics Community Service Team to carry out ecoprint product business management training activities so that it can help entrepreneurs, especially mothers and teenagers who have developed businesses. which he has initiated. Activities are expected to be carried out in a sustainable manner so as to have a positive impact on economic development.